A Study on customer perception towards E-Banking facilities (International Journal of Food and Nutritional Sciences, 2022)
E-banking, also known as electronic banking, is another paradigm shifter that hasrevolutionized the traditional banking system. E-banking is the electronic delivery of bankingservices and transactions through various digital channels such as the Internet, mobile appsand ATMs